Guaranteed green jobs: Sustainable full employment - Antoine Godin (Levy Economics Institute of Bard College, 2012)
In most economies, the potential of saving energy via insulation and more efficient uses of electricity is important. In order to reach the Kyoto Protocol objectives, it is urgent to develop policies that reduce the production of carbon dioxide in all sectors of the economy. This paper proposes an analysis of a green-jobs employer-of-last-resort (ELR) program based on a stock-flow consistent (SFC) model with three productive sectors (consumption, capital goods, and energy) and two household sectors (wage earners and capitalists). By increasing the energy efficiency of dwellings and public buildings, the green-jobs ELR sector implies a shift in consumption patterns from energy consumption toward consumption of goods. This could spur the private sector and thus increase employment. Lastly, the jobs guarantee program removes all involuntary unemployment and decreases poverty while lowering carbon dioxide emissions. The environmental policy proposed in this paper is macroeconomic and offers a structural change of the economy instead of the usual micro solutions.
Keywords: E24; J08; Q48; 330; Full Employment; Green Jobs; Stock-flow Consistent